Air jet impingement technique for thermal characterisation of premixed methane–air impinging flame jets. (25th April 2016) - Kuntikana, Pramod; Prabhu, S.V.
Highlights: Steady state technique is proposed for thermal characterisation of flame jet. Effect of Re, ϕ and Z on Nu and η for impinging flame jets is investigated. Correlations are developed for local Nu and η in terms of flame jet parameters. Thermal efficiency of the burner varies with the flame jet parameters. Abstract: A major part of the domestic and the industrial thermal energy requirement for the heating purpose is achieved by the combustion of hydrocarbon fuels using burners. The present study reveals that thermal characterisation of impinging flame jets can be performed with a steady state technique similar to thin metal foil technique used for impinging air jets. The target surface impinged by the premixed methane–air flame jet is simultaneously cooled from the rear side by impinging air jets at different Reynolds number. One dimensional energy balance across the thickness of the plate is performed. The Nusselt number and the effectiveness distributions for a tube burner with the present technique matched reasonably well with the two-equation technique proposed in our previous work. Maximum deviations of 12% and 15% are observed for Nu and η respectively. Correlations are developed for the local Nusselt number and effectiveness in terms of flame jet parameters. The burner is analysed for the thermal efficiency. For premixed cone flames, it is observed that the thermal efficiency increases with the Reynolds number and equivalence ratio and decreases with the burner tip to plate spacing.